94 Germline Mosaicism – when a rare disease recurs. (30th November 2020) - Lam, Tanya; Rahman, Shamima; Kumar, Ajith
Abstract : Rare autosomal dominant and X linked genetic disorders are often caused by new mutations. Both parents are healthy in these instances and they are counselled that the risk of recurrence in their future children is likely to be low (usually less than 1%). However, in some of these families, one parent may have a mutation confined to some cells including testicular or ovarian cells (germline or gonadal mosaicism). Whilst rare, germline mosaicism may significantly change the risk of recurrence in future offspring, with implications for genetic counselling. We review families who have multiple affected children due to germline mosaicism, discuss conditions in which germline mosaicism is more common and a current study that aims to stratify risk using NGS (Next Generation Sequencing) on multiple cell lines in both parents.